Digital mixing tools in the development of musical skills - Santiago, Glauber Lúcio Alves; Joaquim, Caroline Torkomian (Revista Hipótese, 2022)
The article presents a software, which is the digital audio workstation Cakewalk by BandLab and the website Cambridge Music Technology (section: The 'Mixing Secrets' Free Multitrack Download Library) as tools with high potential educational for free use and with professional quality, in terms of the commercial process of music production. In the end, a list of musical skills based on literature is presented, and suggestions of which the student can improve during the practical activity of mixing phonograms.
Keywords: Mixing; Musical skills; Musical production